Perancangan Sistem Informasi Penggajian Karyawan Berbasis Web Menggunakan Laravel Pada Bms Mart Grosir Herbal Kota Tasikmalaya - Itban Al Mubarak Attasiky; Lita Lestari Utami (Jurnal Tika, 2024)
BMS MART is a company engaged in the sale of various herbs that have been listed in BPOM. The recording process and salary calculation applied by BMS MART are still manual and not modern, which uses handwriting methods and manual calculations. This takes a long time and is less efficient for employees and the owner. In solving this problem, the author designed a web-based employee payroll information system using laravel. In its design, the author uses PHP as its programming language with a MySQL database, using the Waterfall Method, and using the Laravel Framework. With the design that the author has made, it is hoped that the company BMS MART will gain convenience in the process of recording, calculating, and reporting employee payroll and become more efficient and faster